2017
DOI: 10.1186/s12877-017-0653-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinically significant discrepancies between sleep problems assessed by standard clinical tools and actigraphy

Abstract: BackgroundSleep disturbances are widespread among nursing home (NH) patients and associated with numerous negative consequences. Identifying and treating them should therefore be of high clinical priority. No prior studies have investigated the degree to which sleep disturbances as detected by actigraphy and by the sleep-related items in the Cornell Scale for Depression in Dementia (CSDD) and the Neuropsychiatric Inventory – Nursing Home version (NPI-NH) provide comparable results. Such knowledge is highly nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 48 publications
2
38
1
Order By: Relevance
“…The NPI-NH sleep item comes with a description similar to the NPI, followed by six follow-up questions (including "other nighttime behaviors"). Previous studies have suggested a cut-off product score of frequency (1-4) multiplied by severity (1-3) of ≥4 to define the presence of sleep disturbance on this single item from the NPI-NH (25,41). In contrast to the SDI, the NPI-NH followup questions do not ask about excessive daytime sleep (SDI item 7) or if the patient wake up during the night without engaging in any specific behaviors (SDI item 4).…”
Section: Measurementsmentioning
confidence: 99%
See 4 more Smart Citations
“…The NPI-NH sleep item comes with a description similar to the NPI, followed by six follow-up questions (including "other nighttime behaviors"). Previous studies have suggested a cut-off product score of frequency (1-4) multiplied by severity (1-3) of ≥4 to define the presence of sleep disturbance on this single item from the NPI-NH (25,41). In contrast to the SDI, the NPI-NH followup questions do not ask about excessive daytime sleep (SDI item 7) or if the patient wake up during the night without engaging in any specific behaviors (SDI item 4).…”
Section: Measurementsmentioning
confidence: 99%
“…Actigraphs are wrist-worn devices that can measure activity across several days, and even weeks (42). The actigraphs were placed on the dominant wrist, in accordance with previous studies in this population (8,25). Each 1-min epoch was scored as either sleep or wake by the Actiware 6.0.9 (Philips Respironics) software, based on activity from the two epochs immediately preceding and following the relevant epoch.…”
Section: Measurementsmentioning
confidence: 99%
See 3 more Smart Citations